2017
DOI: 10.1142/s1084946717500170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impacts of Starting Up Unregistered on Firm Performance in Africa

Abstract: The aim of this paper is to contribute to an understanding of the entrepreneurship process in Africa by evaluating the link between starting up unregistered and future firm performance. The widespread assumption has been that firms starting up unregistered in the informal economy suffer from poor performance compared to those starting up registered and in the formal economy. To test this poorer performance thesis, World Bank Enterprise Survey (WBES) data is evaluated from across 41 African countries covering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…However, Kappel and Ishengoma (2006) identify the high cost of formalization and the lack of institutional incentives for operating in the formal sector as the main barriers to entry into the formal sector. Williams and Kedir (2017) support this view and explain that because of limited resources, new firms may choose to focus their resources on creating a stronger foundation for their business by investing in building relationships with suppliers or establishing stronger routines, over paying for registration. Empirical studies by Devas and Kelly (2001) and Sander (2003) supported this argument because they found that a reduction in registration cost led to an increase in business registration in Kenya and Uganda, respectively.…”
Section: Barriers To Entry Into the Formal Sectormentioning
confidence: 98%
See 4 more Smart Citations
“…However, Kappel and Ishengoma (2006) identify the high cost of formalization and the lack of institutional incentives for operating in the formal sector as the main barriers to entry into the formal sector. Williams and Kedir (2017) support this view and explain that because of limited resources, new firms may choose to focus their resources on creating a stronger foundation for their business by investing in building relationships with suppliers or establishing stronger routines, over paying for registration. Empirical studies by Devas and Kelly (2001) and Sander (2003) supported this argument because they found that a reduction in registration cost led to an increase in business registration in Kenya and Uganda, respectively.…”
Section: Barriers To Entry Into the Formal Sectormentioning
confidence: 98%
“…In recent years, governments have changed focus and now acknowledge the possible contributions of the informal sector to the economy through taxation and employment creation. There is now more drive by governments to encourage formalization of the enterprises as a way to deal with the informal sector (Williams and Kedir, 2017). Across the world there has been increasing recognition of the informal sector as a key driver of the national economy and that has moved the policy approach from completely eradicating the informal sector to policies that addresses institutional imperfections and institutional asymmetry and encourage formalization instead (Williams and Kedir, 2017;Deakins and Freel, 2009).…”
Section: Why Formalize the Informalmentioning
confidence: 99%
See 3 more Smart Citations